The national curriculum implementation into the operational curriculum based on multiple intelligences theory (Research dissemination before pandemic Covid-19) - Adriana Gandasari; Dinn Wahyudin; Ishak Abdulhak; As’ari Djohar (Universitas Airlangga, 2022)
The purpose of this study is to present an overview of implementation of the national curriculum into the operational curriculum in accordance with the notion of multiple intelligences theory. As data sources, Laboratory Elementary School of Indonesia University of Education, 471 pupils, and 31 teachers participated in the mixed-methods study. Observation, testing, and in-depth indirect communication were used to acquire the data. Observation sheet was used to collect qualitative data on the implementation of the national curriculum into the operational curriculum of the school, Student Self-Multiple Intelligence (SSMI) was used to collect quantitative data on students' Multiple Intelligence scores, and Open-Minded Sharing (OPM) was used to collect quantitative and qualitative data on the impact of the teacher's actions on students. The results demonstrated that the implementation of the national curriculum in the form of an operational curriculum based on multiple intelligences theory showed that the Laboratory Elementary School of Indonesia University of Education is concerned with moral and spiritual values in order to instill noble morals in its pupils, and that it has been successful in assisting its children with the development of various intelligences. We conclude that it has an impact on the characteristics of the school and the learning process which both its own uniqueness.